2011
DOI: 10.1029/2011jc007119
|View full text |Cite
|
Sign up to set email alerts
|

Boundary mixing in lakes: 1. Modeling the effect of shear-induced convection

Abstract: [1] Recent studies in lakes have shown evidence for a strong influence of shear-induced stratification on mixing in turbulent bottom boundary layers (BBLs) on sloping topography. These observations suggest that the periodic near-bottom shear resulting from internal wave motions may lead to alternating periods of gravitationally stable and unstable stratification in the BBL with relevant implications for turbulence and mixing in the entire basin. The impact of these processes for basin-scale mixing is investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 69 publications
8
56
1
Order By: Relevance
“…When calculated using the Shih et al (2005) parametrization, the average diffusivity for the bottom 10 m is K Shih = 6.5(5.6, 7.6) × 10 −5 m 2 s −1 , i.e., nearly an order of magnitude lower than when using Γ = 0.2. Previous studies have suggested such substantial reduction of the mixing efficiency (Γ ≪ 0.2) for energetic mixing near bottoms having slopes similar to that of our sampling site (Umlauf and Burchard, 2011;Becherer and Umlauf, 2011). However, these studies also predict considerably reduced stratification above the seafloor which is not the case in the present observations (Figure 9b suggest a slight increase of the stratification in the bottom 5 m).…”
Section: Mean Turbulent Quantitiessupporting
confidence: 76%
“…When calculated using the Shih et al (2005) parametrization, the average diffusivity for the bottom 10 m is K Shih = 6.5(5.6, 7.6) × 10 −5 m 2 s −1 , i.e., nearly an order of magnitude lower than when using Γ = 0.2. Previous studies have suggested such substantial reduction of the mixing efficiency (Γ ≪ 0.2) for energetic mixing near bottoms having slopes similar to that of our sampling site (Umlauf and Burchard, 2011;Becherer and Umlauf, 2011). However, these studies also predict considerably reduced stratification above the seafloor which is not the case in the present observations (Figure 9b suggest a slight increase of the stratification in the bottom 5 m).…”
Section: Mean Turbulent Quantitiessupporting
confidence: 76%
“…Observations of shear-driven convection in lakes stem from two different single point observations in Lake Alpnach [17] and Lake Constance [4]. The results from these point measurements are consistent with analysis of numerical simulations of shear-driven convection [18], [19], [23]. Nonetheless, to date there are only a few field observations in lakes leaving it unclear as to the relative importance of shear-induced convection versus breaking of NLIW in energizing benthic BBLs.…”
Section: Introductionmentioning
confidence: 57%
“…This process involves the differential advection of stratified waters near a sloping boundary during up- and downwelling events due to internal seiching [4], [17], [18], [19]. During periods of upslope flow, a velocity gradient forms near the boundary, so that away from the boundary layer water is moving faster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider, however, that in view of the near-rectilinear configuration of Windermere that our measurements were reasonably representative of the physical processes operating in a large proportion of the central area of the lake, but future investigations should consider additional observations to account for the spatial variability that may exist in the velocity structure (Hodges et al 2000;Rueda et al 2003;Appt et al 2004;Becherer and Umlauf 2011). Given these extensions of the measurements, there are good prospects for better determinations of energy budgets and consequent improvements in our understanding of lake and shallow sea processes.…”
Section: Summary and Discussionmentioning
confidence: 93%